Pengaruh Moderasi Beragama Dan Kemampuan Analitis Terhadap Quarter Life Crisis - Alviaturrohmah, Lina; Abdan , M. Rohmad (Green Publisher Indonesia, 2025)
The implementation of the concept of religious moderation is very much needed as a multicultural solution in Indonesia, because Indonesia was born as a multicultural country. Individual analytical skills are needed to analyze the right actions to take. The quarter life crisis is currently a common phenomenon. This study aims to see the effect of diverse moderation and individual analytical skills on the quarter life crisis. The respondents in this study were 53 people from class XII MAN Pacitan in the 2024/2025 Academic Year. The results of the study showed that religious moderation had an effect on the quarter life crisis, and religious moderation and analytical skills together influenced the individual's quarter life crisis.